Understanding Customer Intention to Use Online Food Delivery Services In The Post-Pandemic Era In Indonesia - Sugiharto, Cliff Adam; Cahyu Lestari, Himawati; Lamisi Kananda, Ishmael; Ramadhan, Fadhil; Salsabila, Syifa (Dinasti International Journal of Management Science, 2024)
This study aims to explore the factors influencing consumer attitudes and intentions towards using Online Food Delivery (OFD) services in Indonesia. Integrating the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Theory of Planned Behavior (TPB), the research evaluates dimensions such as performance expectancy, effort expectancy, social influence, information quality, price-saving, and time-saving orientation. Through a structured online survey of 275 Indonesian respondents, it was found that social influence, price-saving, and time-saving orientation positively impact OFD perceptions. This study provides novel insights into post-COVID-19 pandemic OFD research in Indonesia, albeit limited to respondents in the Jabodetabek area.